2011
DOI: 10.1038/jp.2011.103
|View full text |Cite
|
Sign up to set email alerts
|

Comparing sound measurements in the single-family room with open-unit design neonatal intensive care unit: the impact of equipment noise

Abstract: Objective: To determine if measured sound levels in the occupied level 3 single-family room (SFR) neonatal intensive care unit (NICU) will be significantly and perceptibly different from the occupied level 3 open-unit (OU) NICU.Study Design: Case-control. Comparison of sound measurements obtained with varying types of respiratory support in SFR unit with measurements obtained from OU level 3 bedside NICU.Result: SFR sound measurements were quieter and less loud compared with the open unit, except when high-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…Since it is the large unit, it has a considerably larger multidisciplinary staff, more traffic from ancillary support and visitors, and more equipment in use, which contribute to the overall noise levels than do smaller units. Other studies comparing single-room NICU with open-unit NICU (similar to NICU A, B and C) revealed higher noise levels mostly in open-units [26,27]. Basner et al [5] stated that noise levels in hospitals are now typically more than L Aeq 15-20 dB higher than those recommended which is in agreement with the majority of the obtained results ( Table 2).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Since it is the large unit, it has a considerably larger multidisciplinary staff, more traffic from ancillary support and visitors, and more equipment in use, which contribute to the overall noise levels than do smaller units. Other studies comparing single-room NICU with open-unit NICU (similar to NICU A, B and C) revealed higher noise levels mostly in open-units [26,27]. Basner et al [5] stated that noise levels in hospitals are now typically more than L Aeq 15-20 dB higher than those recommended which is in agreement with the majority of the obtained results ( Table 2).…”
Section: Discussionsupporting
confidence: 81%
“…In fact, several studies showed that -private room‖ or single-room NICU environment has been the most effective way to address sound issues, especially when used in conjunction with a cultural change among the staff [26,27]. Lastly, regardless of the adjustment period of the operational management in NICU to deal with the new design [35], these singleroom NICU also seems to improve staff satisfaction regarding physical environment and working conditions [36].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of decreased auditory exposure in this study is consistent with other studies reporting diminished sound in the NICU private room. 3,28 …”
Section: Discussionmentioning
confidence: 99%
“…Higher physical demands and workloads placed on nurses could negatively affect the level of care provided. Additional key physical characteristics include internal and external noise [50,51], temperature control, exposure to light [52,53], practice of developmentally supportive care [54], provision and extent of family-centered care, provision and extent of breastfeeding support, potential for continuous parental involvement, as well as training and preparation for discharge home.…”
Section: Methodsmentioning
confidence: 99%